MACHINE LEARNING AND AI WITH .NET CORE: A COMPREHENSIVE GUIDE - Jagdip Keshavlal Jadav (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This comprehensive article explores the integration of Machine Learning and Artificial Intelligence capabilities within the ASP.NET Core framework, examining its transformative impact across various industries. The article investigates performance metrics, implementation strategies, and best practices for deploying ML-powered applications. It details how organizations across healthcare, finance, retail, and transportation sectors have leveraged these technologies to achieve significant operational improvements. The article covers the framework's foundational architecture, ML.NET implementation patterns, and crucial considerations for security and scalability. Through detailed examination of real-world implementations, this article demonstrates how ASP.NET Core's integration with ML and AI has revolutionized application development while establishing new benchmarks for performance and efficiency in enterprise-scale deployments.